Recent Updates on the Potential of Medicinal Plants from Indonesia as Anti-Atherosclerotic Agents - Prasesti, Gayuk Kalih; Narsa, Angga Cipta; Rijai, Akhmad Jaizzur; Lestari, Kharina Septi; Zulkaida, Zulkaida (Universitas Islam Negeri Alauddin Makassar, 2024)
Atherosclerosis is one of the causes of problems in the cardiovascular system. This condition can be prevented by using natural products, one of which is medicinal plants. This review collects data on medicinal plants that are easily found in Indonesia that can reduce or improve atherosclerosis conditions. There are 10 plants reviewed that have a high level of safety and potential to be developed as medicine. The plant parts used are fruit and leaves. Some are commonly used as cooking spices such as turmeric and garlic which are found to be useful for improving atherosclerosis conditions. In the context of modern drug development, Indonesia holds significant potential for exploring these plants as sources of active compounds for pharmaceutical applications. Scientific studies of these natural materials are crucial for identifying bioactive components and understanding their mechanisms of action. With the right approach, Indonesia's natural resources could form the basis for developing new, safer, and more effective drugs. Additionally, Indonesia has a considerable opportunity in the global market for natural health products, including nutraceuticals and dietary supplements, as global interest in natural health solutions continues to grow.